The odd life of Timothy Green - Hedges, Peter; Sanders, Scott; Zappa, Ahmet; Whitaker, Jim, 1968-; Garner, Jennifer, 1973-; Edgerton, Joel, 1974-; Adams, CJ.; Wiest, Dianne; Walt Disney Pictures; Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Disney : Distributed by Buena Vista Home Entertainment, 2012)
When a childless couple buries a box with all of their wishes for an infant in their backyard, their wishes are granted. However, their child, Timothy Green, is not all that he appears.
Special features: deleted scenes; music video performed by Glen Hansard.
Originally released as a motion picture in 2012.
Director of photography, John Toll ; editor, Andrew Mondshein ; music, Geoff Zanelli.
Joel Edgerton, Jennifer Garner, CJ Adams, Dianne Wiest, Rosemarie DeWitt, Ron Livingston.
MPAA rating: PG; for mild thematic elements and brief language.
DVD; NTSC, region 1; widescreeen (1.85:1); Dolby Digital 5.1.
Keywords: Wishes -- Drama; Child rearing -- Drama; Parent and child -- Drama; Fantasy films; Comedy films; Feature films; Films for the hearing impaired; Films for people with visual disabilities